Intravenous contrast-enhanced CT can be used for CT-based attenuation correction in clinical (111)In-octreotide SPECT/CT - Klausen, Thomas Levin (EJNMMI Phys, 2015)
BACKGROUND: CT-based attenuation correction (CT-AC) using contrast-enhancement CT impacts (111)In-SPECT image quality and quantification. In this study we assessed and evaluated the effect. METHODS: A phantom (5.15 L) was filled with an aqueous solution of In-111. Three SPECT/CT scans were performed: (A) no IV contrast, (B) with 100-mL IV contrast, and (C) with 200-mL IV contrast added. Scan protocol included a localization CT, a low-dose CT (LD), and a full-dose CT (FD). Phantom, LD and FD scan series were performed at 90, 120, and 140 kVp. Phantom data were evaluated looking at mean counts in a central volume. Ten patients referred for (111)In-octreotide scintigraphy were scanned according to our clinical (111)In-SPECT/CT protocol including a topogram, a LD (140 kVp), and a FD (120 kVp). The FD/contrast-enhanced CT was acquired in both arterial (FDAP) and venous phase (FDVP) following a mono-phasic IV injection of 125-mL Optiray (4.5 mL/s). For patient data, we report image quality, Krenning scores, and mean/max values for liver and tumor regions. RESULTS: Phantoms: in uncorrected emission data, mean counts (average ± SD) decreased with increasing IV concentration: (A) 119 ± 9, (B) 113 ± 8, and (C) 110 ± 9. For all attenuation correction (AC) scans, the mean values increased with increasing iodine concentration. Patients: there were no visible artifacts in single photon emission computed tomography (SPECT) following CT-AC with contrast-enhanced CT. The average score of image quality was 4.1 ± 0.3, 3.8 ± 0.4, and 4.2 ± 0.4 for LD, arterial phase, and venous phase, respectively. A total of 16 lesions were detected. The Krenning scores of 13/16 lesions were identical across all scan series. The max pixel values for the 16 lesions showed generally lower values for LD than for contrast-enhanced CT. CONCLUSIONS: In (111)In-SPECT/CT imaging of phantoms and patients, the use of IV CT contrast did neither degrade the SPECT image quality nor affect the clinical Krenning score. Reconstructed counts in healthy liver tissues were unaffected, and there was a generally lower count value in lesions following CT-AC based on the LD non-enhanced images. Overall, for clinical interpretation, no separate low-dose CT is required for CT-AC in (111)In-SPECT/CT.